Tradeoffs between in- and out-of-residential neighborhood locations for discretionary activities and time use: do social contexts matter?. (July 2015) - Lin, Tao; Wang, Donggen
Highlights: Study of how social contexts impact location choices for discretionary activities. The tradeoffs between in- and out-of-neighborhood locations are examined. Models are developed using activity-diary survey data collected in Beijing in 2013. Neighborhood social contacts influence discretionary activities location choices. Neighborhood safety and social cohesion induce more in-neighborhood activities. Abstract: Individuals' decisions about where to spend time and conduct their daily activities have significant implications for trip generation and travel demand. Factors that may influence such decisions, including individuals' socio-demographics and the built environment of their residential place, have been examined in previous studies. However, characteristics of personal social networks and the social environment of residential neighborhoods have not received much attention. We argue that these social context factors may determine the tradeoffs between choosing a residential neighborhood or other places for daily activities, especially discretionary activities. Using data from an activity–travel diary survey conducted in Beijing in 2013, we examine and model the importance of personal social networks and residential neighborhood social environment variables in the choice of location and time allocation for discretionary activities. Our findings suggest that the size, nature and spatial ordering of personal social networks significantly influence individuals' tradeoffs between activities and time use in and out-of residential neighborhoods. This study will contribute to the growing literature on social network and activity–travel behavior.